The Impact of Media on Consumers' Environmental Behaviour - Gregor Jagodic (International School for Social and Business Studies, 2016)
People, companies and society are becoming more mindful about the environment, and thus the market demand environmentally-sustainable merchandises and services. Today consumers act more pro-environmentally, as in the past decades they have changed their behaviour. We all recognise that the development of different types of media, especially the Internet and social media, has generated a different approach from societies and traders towards the individual consumer. In this research, we have established that the Internet, social media and TV have at the moment the largest influence on consumers' environmental behaviour, due to the fact that companies and marketers are targeting at the same time different target groups of consumers. In the case of the Internet or social media, the marketers are very aggressive, although many consumers have the sense that they are something special for the companies and, therefore, change their environmental behaviour following the marketers and companies' desires.